2001
DOI: 10.1677/joe.0.1710033
|View full text |Cite
|
Sign up to set email alerts
|

Novel expression of the stanniocalcin gene in fish

Abstract: It is currently accepted that the fish stanniocalcin (STC) gene is expressed exclusively in the corpuscles of Stannius (CS), unique endocrine glands on the kidneys of bony fishes. In this study, we have re-examined the pattern of fish STC gene expression in the light of the recent evidence for widespread expression of the gene in mammals. Surprisingly, we found by Northern blotting that the fish gene was also expressed in the kidneys and gonads, in addition to the CS glands. Moreover, Southern blotting of RT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 34 publications
0
20
1
1
Order By: Relevance
“…The gene for coho and chum salmon STC has been sequenced (779,842), and initial studies on the distribution of the STC mRNA and product suggested that they are expressed only in cells in the CS in fishes (439,713). However, more recent in situ hybridization and Northern blot studies have delineated STC expression in a variety of tissues in the rainbow trout and arawana (Osteoglossum bicirrhosum), including the kidney and gills (4,478), suggesting that STC may act as a paracrine as well as circulating hormone. Interestingly, two distinct STCs are expressed in the CS of the Atlantic salmon (782).…”
Section: Stanniocalcinmentioning
confidence: 99%
“…The gene for coho and chum salmon STC has been sequenced (779,842), and initial studies on the distribution of the STC mRNA and product suggested that they are expressed only in cells in the CS in fishes (439,713). However, more recent in situ hybridization and Northern blot studies have delineated STC expression in a variety of tissues in the rainbow trout and arawana (Osteoglossum bicirrhosum), including the kidney and gills (4,478), suggesting that STC may act as a paracrine as well as circulating hormone. Interestingly, two distinct STCs are expressed in the CS of the Atlantic salmon (782).…”
Section: Stanniocalcinmentioning
confidence: 99%
“…The fish STC gene, about 4 kb long, has been isolated from sockeye salmon (McCudden et al 2001a), and contains five exons. From comparative alignment of the gene structures (Fig.…”
Section: Chromosomal Localization and Genomic Structurementioning
confidence: 99%
“…The existence of mammalian STC1 mRNA in a wide variety of tissues was regarded as strikingly different to fish STC, as the www.endocrinology.org 361 latter was thought to be expressed exclusively in the unique endocrine gland, the CS. These observations led to a re-examination of fish STC gene expression (McCudden et al 2001a). Northern blotting of poly(A+) RNA detected STC mRNA in testis, ovary and anterior kidney at levels about 100-fold lower than in the CS, which may explain why they had been overlooked previously.…”
Section: Stc1 Mrna and Protein Expressionmentioning
confidence: 99%
“…In response to an increase in blood Ca 2C level, the CaSR-mediated STC1 release from CS glands inhibits gill Ca 2C uptake to restore homeostasis (Greenwood et al 2009, Lin et al 2014. Intriguingly, a re-examination of stc1 gene expression in fish tissues revealed the presence of stc1 transcript in gills of trout (McCudden et al 2001). Moreover, the expression of stc1 in gills of Japanese flounder was found to be stimulated by water salinity and Ca 2C (Shin & Sohn 2008 …”
Section: Cmentioning
confidence: 99%